13. THE CURRENT SITUATION AND SOME FACTORS RELATED TO SIGNS OF ANXIETY, DEPRESSION, AND STRESS AMONG PHENIKAA HEALTH SCIENCES STUDENTS IN THE COVID-19 PANDEMIC, 2021 (Vietnam Journal of Community Medicine, 2023)
Background: A cross-sectional study was conducted on 369 full-time health sciences studentsstudying at Phenikaa University to find out about the status and some factors related to the signs ofanxiety, depression, and stress among students during the COVID-19 pandemic.Results: The prevalence of students with anxiety, depression, and stress was (11.1%), (11.1%)and (4.9%) respectively. Factors, such as male gender and history of psychological problems(psychological stress, anxiety disorders, depression, sleep disturbances), were identified to affect thepsychology of female students during the COVID-19 pandemic.Conclusion: The percentage of students showing signs of anxiety, depression, and stress is relativelyhigh in this study, indicating the support plans and extracurricular programs from school to helpstudents release and balance their psychological health to improve the above situation.
Keywords: Phenikaa, anxiety, depression, stress, students, DASS-21.